2002
DOI: 10.1088/0953-4075/35/4/303
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering of low-energy electrons by NF3

Abstract: We present results of e--NF3 collision calculations for energies up to 60 eV. To compute the elastic integral, differential, and momentum-transfer cross sections we have employed the Schwinger multichannel method implemented with norm-conserving pseudopotentials (Bettega M H F, Ferreira L G and Lima M A 1993 Phys. Rev. A 47 1111) within the fixed-nuclei static-exchange approximation. We have compared our results with the complex Kohn results of Rescigno and with the experimental data of Boesten et al, and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The experimental data by Boesten et al 15 is not complete, especially, at energies below 1 eV. Out of the three theoretical studies 22,23,25 , the most recent one by Hamilton et al 25 appears to be the most accurate one due to a more accurate method (complete active space-configuration interaction) and a larger basis set employed. However, the position of the resonance near 1 eV in this study is shifted towards lower energies compared to the experimental data.…”
Section: Momentum Transfer Cross Sectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental data by Boesten et al 15 is not complete, especially, at energies below 1 eV. Out of the three theoretical studies 22,23,25 , the most recent one by Hamilton et al 25 appears to be the most accurate one due to a more accurate method (complete active space-configuration interaction) and a larger basis set employed. However, the position of the resonance near 1 eV in this study is shifted towards lower energies compared to the experimental data.…”
Section: Momentum Transfer Cross Sectionmentioning
confidence: 99%
“…• , was published by Boesten et al 15 Subsequently, a Schwinger multichannel theoretical approach 23 reported corresponding cross sections for 14 . Values at 100-500 eV are obtained from parameters of the BetheBorn plot, Fig.…”
Section: Elastic Scattering Cross Sectionmentioning
confidence: 99%
See 3 more Smart Citations